Efektivitas Memberdayakan Ekonomi Pada Program Komunitas Usaha Mikro Muamalat Berbasis Masjid di Masjid Miftahul Jannah Surabaya - Hanif Ardiansyah; Muhammad Nafik HR (Universitas Airlangga, 2014)
The porpose of this research is to find out the effectiveness of Mosque-basedMicrobusiness Community Program to empowering mustahiq’s economy at Miftahul Jannah Mosque Surabaya.The research method of this research is a qualitative approach, case studies strategy, and descriptive analysis techniques which collecting data through interview, and observation. The informants are members of Mosque-based Microbusiness Community Program at Miftahul Jannah Mosque Surabaya, consist of seven people who had attanded the program and has recieved assistance zakat productive in the form venture capital from Baitul Maal Muamalat through Mosque-based Microbusiness Community Program (KUM3).Based on the results of the research is Mosque-based Microbusiness Community Program effective to empower mustahiq’s economy use productive zakat consist of venture capital, the mosque has a maximum role to facilitate the distribution of productive zakat from Baitul Maal Muamalat to mustahiq evidenced by increasing three indicators, namely ruhiyah, partisipation, and business. REFERENCES Al Qur’an Al Karim.Antonio, M. Syafi’i. 1999. Bank Syaria: Wacana Ulama dan Cendekiawan. Jakarta:Tazkia Institute.Arens,Alvin A.J.K Loebbecke.2001. Auditing Suatu Pendekatan Terpadu. Jakarta: Airlangga.Asnaeni. 2010. Membangun Zakat Sebagai Upaya Membangun Masyarakat. Jurnal La_Riba. Volum IV, no. 1.Djazuli, A. 2002. Lembaga-Lembaga Perekonomian Umat. Jakarta: PT.Raja Graindo Persada.Hafidhudin, Didin. 1998. Panduan Praktis Tentang Zakat, Infaq, Shadaqah. Jakarta: Gema Insani.. 2006. Panduan Zakat Praktis. Jakarta: Dompet Dhuafa Republika.. 2007. Agar Harta Berkahdan Bertambah Gerakan Memberdayakan Zakat, Infaq, Shadaqah. Jakarta: Gema Insani.Jhingan, M.I. 2004.Ekonomi Pembangunan dan Perencanaan.Jakarta : PT. Raja Grafindo Persada.Kunarjo. 2002. Perencanaan dan Pengendalian Program Pembangunan. Jakarta: UI press.Mufraini, M. Arif. 2006. Akuntansi dan Manajemen Zakat: Mengkomunikasikan Kesadaran dan Mengembangkan Jaringan. Jakarta: Kencana.Qardhawi, Yusuf. 1991. Hukum Zakat. Jakarta: Lentera.. 1995. Kiat Islam MengentaskanKemiskinan. Jakarta: GemaInsani Press.. 1996. Hukum Zakat Studi Komparasi Mengenai Status danFilsafat Zakat Berdasar AlQur’an dan Hadist. Jakarta: Mizan.. 2005. Spektrum Zakat dalamMengembangkanEkonomiK erakyatan (terj.). Jakarta: Zikrul Hakim.Ryandono, Muhamad Nafik Hadi. 2008. Ekonomi Ziswaq(Zakat, Infaq, Shadaqah, dan Waqaf). Surabaya: IFDI dan cenforis.Sugiyono. 2011. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung:Alfabeta.Tyson,Shaun& Tony jakson.2000. The Essence of Organizational. Yogyakarta: ANDIYin. 2002. Studi Kasus Desain & Metode. Jakarta: PT Grafindo Persada. Yuliana,Indah. 2012. Implementasi Pendistribusian Dana Zakat, Infaq,dan Shadaqah Perbankan Syariah Untuk Pemberdayaan Usaha Kecil Mikro di Malang.Artikel. Malang: UIN Maulana Malik Ibrahim.